Metazoarios ectoparásitos en ejemplares de sábalo cola roja Brycon amazonicus provenientes del medio natural y de estanques de cultivo, Loreto-Perú - Ampuero Solsol, Ximena Stefani (2022)
The main objective of the present work was to know the ectoparasitic metazoans that parasitize the "sabalo” B. amazonicus from the natural environment and from culture ponds of the Fernando Alcántara Research Center (CIFAB) of the IIAP, between the months of March to June 2021. It was carried out by means of the observation, search and identification of the ectoparasitic fauna of Brycon amazonicus.The analysis of the fish was carried out in the Laboratory of Parasitology and Aquaculture Health of the IIAP In the present study, 9 species of Monogenoidea (Anacanthorus sp1, sp2, sp3, sp4, A spiralocirrus, A. femoris, A sabalai, A kukamensis and A. rarus), 1 species of Copepoda (Ergasilus bryconis) and 1 species of Branchiura (Argulus multicolor). These data belong to the specimens from the In the natural environment, in the case of specimens from culture ponds, only two species of Monogenoidea were found, which are A. spiralocirus and A femons. Likewise, the similarity of individuals and species was determined, obtaining a result of 30% similarity in numbers of species in the qualitative aspect and 43% in number of individuals in the quantitative field; Regarding the parasitic indices (prevalence, intensity, average intensity and average abundance), the species of Monogenoidea Anacanthorus femoris collected in B amazonicus from the natural environment is the dominant one in these indices with a prevalence of 90%, intensity of 234 individuals, mean intensity of 8.67 and mean abundance of 7.80 Concluding that the ectoparasites present in B. amazonicus are mostly composed of Monogenoidea species, with a high diversity of species in specimens from the natural environment.